Early Bortezomib Therapy for Refractory Anti-NMDA Receptor Encephalitis - Turnbull, Marion T.; Siegel, Jason L.; Becker, Tara L.; Stephens, Alana J.; Lopez-Chiriboga, A. Sebastian; Freeman, William D. (Frontiers in Neurology, 2020)
Introduction: Anti-NMDA receptor encephalitis is an increasingly recognized syndrome of neuropsychiatric disturbances that can be auto-immune in origin or associated with paraneoplastic conditions. Here we present a case that represents the shortest hospitalization-to-bortezomib treatment timeline (42 days), and we believe this is reflected in the patients’ outcome with complete independence within a short timeframe. Case Report: We describe a case of anti-NMDA receptor encephalitis in an 18-year-old African American female presenting with progressive, medically refractory disease. Despite two rounds of high dose intravenous steroids, plasma exchange, immunoglobulin (IVIG) administration, and rituximab for B-cell depletion, the patient failed to respond by hospital day 42 and received off label use of the proteasome inhibitor, bortezomib. During the 15 days after bortezomib administration, the patient showed dramatic neurologic recovery that allowed transfer out of the intensive care unit. At a one-month follow up the patient reported feeling normal cognitively and showed dramatic improvement in cognitive scores. Conclusion: This case and literature review provide preliminary evidence that early treatment of anti-NMDA receptor encephalitis with the proteosome inhibitor bortezomib appears safe and tolerable. However randomized trials are needed to show efficacy and long term benefit.